(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Determination of the proper vertical dimension during prosthesis construction is of paramount importance in treating patients with missing teeth. This study was conducted to correlate the measurement of finger length with occlusal vertical dimension. MATERIALS AND METHODS: An analytical cross-sectional study was conducted in the Department of Prosthodontics, Tribhuvan University Teaching Hospital, Maharajgunj, Kathmandu, Nepal among 145 MBBS and BDS students. Length of four fingers and vertical occlusal dimension were measured by two anatomical methods with the use of vernier calipers. Data were analysed in SPSS version 20. Mean, standard deviation, frequency and percentage were calculated depending upon the nature of data. Pearson’s correlation was used to determine the relation between finger length with vertical occlusal dimension. RESULTS: Moderate positive correlation was found between occlusal vertical dimension (OVD) measuring tip of nose to gnathion and base of nose to menton with all four fingers (p<0.001 each). When compared for males and females, significant moderate correlation was found between OVD by both methods and anthropological measurements in all the four fingers in males (p<0.001 each) but only with index finger when OVD was measured from tip of nose to gnathion in females (p<0.001). CONCLUSIONS: The findings of this study concluded that all four fingers may be used for determination of OVD in males but only index finger may be used in females.